Description of one new species of freshwater shrimp of the genus Caridina (Crustacea: Decapoda: Atyidae) from two karst caves of Northern Vietnam - Tu, Do Van; Dong, Dang Van; Rintelen, Thomas Von (Zootaxa, 2021)
A new species of atyid freshwater shrimp is described from two caves of Bac Kan Province, Northeast Vietnam, namely Caridina namdat sp. nov. This species can be distinguished from its congeners by a suite of morphological characters such as reduced eyes with short eyestalk, very short and unarmed rostrum, slender second pereiopod, elongated endopod of male first pleopod, and long appendix interna of the male second pleopod. Molecular phylogenetic data from the mitochondrial cytochrome oxidase subunit I (COI) and 16S ribosomal RNA genes also support the distinctiveness of the new species from all other examined species.